MERDEKA CURRICULUM FOR HIGH SCHOOL ENGLISH LEARNING IN THE DIGITAL ERA - Rohimajaya, Nur Azmi; Hamer, Welliam (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
The digital era is a digital education environment where technical resources support teaching and learning. To determine educational performance, the curriculum must be adaptive to all contemporary concerns and changes. Following several curriculum reforms, the Merdeka Curriculum is currently being implemented in Indonesia. The Indonesian government has fully changed the curriculum possible to complete the educational goals anticipated in this digital era. This study compares the 2013 curriculum to the Merdeka curriculum for learning English at the senior high school level in terms of the basic framework, targeted competencies, curriculum structure, learning, assessment, teaching materials, and curriculum tools. The research design used in this study is a qualitative approach with content analysis. Based on the basic framework, targeted competencies, curriculum structure, learning process, assessment, teaching resources, and curriculum tool, this study shows similarities and differences between the 2013 and Merdeka curriculum.